Fish canning handbook - Bratt, L. [ (Les)] (Blackwell Publication, 2010)
Canning continues to be an extremely important form of food preservation commercially, and canned fish represents a source of relatively inexpensive, nutritious and healthy food which is stable at ambient temperatures, has long shelf life and in consequence is eminently suitable for worldwide distribution.